If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 67 + 92x = 92 Solving 67 + 92x = 92 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-67' to each side of the equation. 67 + -67 + 92x = 92 + -67 Combine like terms: 67 + -67 = 0 0 + 92x = 92 + -67 92x = 92 + -67 Combine like terms: 92 + -67 = 25 92x = 25 Divide each side by '92'. x = 0.2717391304 Simplifying x = 0.2717391304
| 2/4+2/4+x=3 | | 4/3=5/8a+14/3 | | -5x-3(3x+10)=138 | | -3(2x-3)=4(5-x) | | 2(3z-1)=16 | | 3(x-8)=7 | | 3x+8x-14=30 | | 3(x-4)+37=2x | | 1.3y+7.8=1.3 | | 5x-6=5*5+3 | | -4w+4=0 | | 6x+2-3x+9=0 | | x/2+x/3*4=5 | | -2x-6(3x+10)=40 | | 14+2y=2(y+3) | | (5x-4)(3x+2)=0 | | 100+10=x+15 | | 7(x+4)+8=8(2x-6) | | 5r=16-(2r+8) | | 9-x+2=2x+3x | | 4x-4(x+4)=5(x+4) | | 2(3(-3)-2)+-3=9 | | (3x-5)(9x+7)=0 | | 2x-5(3x-8)=118 | | 7x+8-10x-12=9x-6x+8 | | 10(2x-4)+20=5(4x-3)+18+3x | | 6a+7-a=-17 | | -4(2x-3)=4x-18+3x | | 1/3X^2+4X+1=0 | | 6s-10=s-2 | | x^2-24x-64=0 | | -5x-3(-6x-13)=117 |